Efektivitas Metode Gallery Walk Berbasis 4C dalam Pembelajaran IPA di Sekolah Dasar - Muhammad Shokhid; Bahauddin Azmy; Dian Kusmaharti (Journal of Edukasi Borneo, 2020)
This study aimed to examine the effectiveness of the 4C-based gallery walk method on science learning outcomes on the subject of digestive organ disorders of fifth-grade students in one of the public elementary schools (SDN) in Surabaya. Quasy-Experimental with posttest-only control design was employed. The population of this research was the fifth-grade students of SDN in Surabaya. The sample was taken by a purposive sampling technique so that the V-C class (experimental class) and V-D (control class) were obtained. Data collection techniques used were student learning outcomes tests. The data analysis technique used a t-test with the help of Microsoft Excel tools, with a significance level of 5% (α = 0.05). The results of the calculation of the results of data processing using the t-test assisted by Microsoft Excel tools in the previous sub-chapter which showed the value of t-count = 8.58> t-table = 3.8, then H0 was rejected, explaining that there was an effect on the learning outcomes test for the VC experimental class and the control class. VD, meaning that there was an effect of using the 4C-based gallery walk method on the learning outcomes of natural science learning outcomes for grade V SDN students. ABSTRAK Penelitian ini bertujuan untuk menguji efektivitas metode gallery walk berbasis 4C terhadap hasil belajar IPA pada materi gangguan organ perncernaan siswa kelas V di salah satu sekolah dasar negeri (SDN) Surabaya. quasy experimental dengan Posttest-Only Control Design digunakan. Populasi penelitian ini adalah siswa kelas V SDN di Surabaya. Sampel diambil dengan teknik purposive sampling sehingga didapatkan kelas V-C (kelas eksperimen) dan V-D (kelas kontrol). Teknik pengumpulan data yang digunakan yaitu tes hasil belajar siswa. Teknik analisis data dengan menggunakan t-test dengan berbantu alat Microsoft Excel. dengan taraf signifikansi 5% ( = 0,05). Hasil perhitungan hasil pengolahan data mengunakan t-test berbantuan alat Microsoft Excel pada sub bab sebelumnya yang menunjukan nilai t-hitung = 8.58 > t-tabel = 3.8, Maka H0 di tolak sehingga menjelaskan bahwa ada pengaruh tes hasil belajar kelas eksperimen V-C dan kelas kontrol V-D, artinya ada pengaruh penggunaan metode gallery walk berbasis 4C terhadap hasil belajar IPA gangguan organ perncernaan siswa kelas V SDN. Kata Kunci: gallery walk berbasis 4C, SDN, IPA, hasil belajar.